INOVASI PERTANIAN: SCARECROW PINTAR BERBASIS ESP32 UNTUK MENGUSIR HAMA SECARA OTOMATIS DI DESA TEGAL WARU KECAMATAN CIAMPEA - Ernawati, Erna; Kelana, Sukma; Aristian; Amalia; Latifah, Euis; Hayya A.K, Husniatu; Faulina B.L, Nahdiah; Anita, Cacan; Gunawan, Gugun (Sahid Mengabdi: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2024)
This research aims to develop and implement an ESP32-based smart scarecrow as an innovative solution in overcoming the problem of sparrow and rat pests in Tegal Waru Village, Ciampea District. This research uses an experimental method to design, build, and test a prototype bird pest repellent tool based on ESP32, PIR and ultrasonic sensors to detect the presence of pests, then repel them with environmentally friendly ultrasonic speakers. The system also utilizes solar power as an energy source, thus supporting environmental sustainability and reducing the use of chemical pesticides. The results showed that the smart scarecrow was effective in reducing crop damage by 85% and increasing yields. In addition, this technology also helps improve farmers' welfare by lowering operational costs and providing convenience in pest control through mobile applications. Thus, the ESP32-based smart scarecrow offers a practical and sustainable solution for modern agriculture.